The Review of Fundamental Framework for Reflective Thinking and Practice in Science Education: Implications for Transformative Science Learning - Nurhayati, Pipih; Widodo, Ari; Syamsudin, Achmad (Universitas Negeri Semarang, 2023)
The primary objective of this study is to establish a fundamental framework for reflective thinking and practice in science education that can contribute to transformative learning worldwide. The study utilized the SPIDER inclusion criteria to select relevant articles from SCOPUS and WoS databases in March 2023, which included sample, phenomenon of interest, design, evaluation, and research type. The PRISMA framework was also used, which consisted of four steps: identification, screening, eligibility, and inclusion. In the end, the study analyzed 52 articles using Biblioshiny as a tool for analysis. The results indicated that Reflective Practice, International Journal of Science Education, and Education Sciences are the most commonly used sources for research on this topic. Turkey and the USA have shown the highest productivity in terms of research on reflective thinking. The frequency of the term